2004
DOI: 10.1128/jcm.42.6.2480-2488.2004
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing Is a Reliable Alternative Method to DNA Fingerprinting for Discriminating among Strains of Candida albicans

Abstract: Multilocus sequence typing (MLST) has emerged as a powerful new DNA-typing tool for the evaluation of intraspecies genetic relatedness. This method relies on DNA sequence analysis of nucleotide polymorphisms in housekeeping genes and has shown a high degree of intraspecies discriminatory power for bacterial and fungal pathogens. However, the results of the MLST scheme for Candida albicans have heretofore never been formally compared to those of other established typing techniques. To assess the value of MLST r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 32 publications
3
56
1
2
Order By: Relevance
“…The percent concordance between any two typing techniques for a particular set of isolates was calculated as previously described with cross-classification analysis of all possible pairs of those isolates (22,38,39). Simpson's index of diversity, which indicates the probability that among a group of isolates any two randomly selected isolates will have different genotypes (19), was used to measure discriminatory power.…”
Section: Methodsmentioning
confidence: 99%
“…The percent concordance between any two typing techniques for a particular set of isolates was calculated as previously described with cross-classification analysis of all possible pairs of those isolates (22,38,39). Simpson's index of diversity, which indicates the probability that among a group of isolates any two randomly selected isolates will have different genotypes (19), was used to measure discriminatory power.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the portability of MLST data allows results from different laboratories to be compared (33,34). MLST was first utilized to genetically characterize pathogenic bacteria but has now been expanded for use in genetic and population studies of fungi and protozoa (48,67).…”
mentioning
confidence: 99%
“…An agreed consensus scheme between the different laboratories examined seven loci, AAT1a, ACC1, ADP1, MPIb, SYA1, VPS13, and ZWF1b, and allowed the application of MLST to the analysis of C. albicans epidemiology and population structure (7-9, 16, 36, 52). MLST analysis has since been demonstrated to be as sensitive as DNA fingerprinting (43), and due to the nature of the data (i.e., DNA sequences of specific loci), these can be used to create a large database generated by multiple laboratories (7). In the case of C. albicans, it has also been shown that the strain groupings identified by MLST correlate with clades of C. albicans organisms identified using the species-specific DNA fingerprinting probe Ca3 (52).…”
mentioning
confidence: 99%